2015
DOI: 10.1186/s12995-015-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Subjective stress, objective heart rate variability-based stress, and recovery on workdays among overweight and psychologically distressed individuals: a cross-sectional study

Abstract: BackgroundThe present study aimed to investigate how subjective self-reported stress is associated with objective heart rate variability (HRV)-based stress and recovery on workdays. Another aim was to investigate how physical activity (PA), body composition, and age are associated with subjective stress, objective stress, and recovery.MethodsWorking-age participants (n = 221; 185 women, 36 men) in this cross-sectional study were overweight (body mass index, 25.3–40.1 kg/m2) and psychologically distressed (≥3/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“…Elixir study was a multi-centre lifestyle intervention aimed to enhance the psychological well-being of 339 individuals with overweight/obesity and self-reported stress symptoms 19 . In this study, higher perceived stress was associated with less physical activity 20 and unfavourable eating behaviours, such as higher dependency on emotional and rewarding properties of food rather than physiological hunger cues and less consumption of wholegrain products 21 . Conversely, study participants with higher physical activity recovered better from stress 22 .…”
mentioning
confidence: 61%
“…Elixir study was a multi-centre lifestyle intervention aimed to enhance the psychological well-being of 339 individuals with overweight/obesity and self-reported stress symptoms 19 . In this study, higher perceived stress was associated with less physical activity 20 and unfavourable eating behaviours, such as higher dependency on emotional and rewarding properties of food rather than physiological hunger cues and less consumption of wholegrain products 21 . Conversely, study participants with higher physical activity recovered better from stress 22 .…”
mentioning
confidence: 61%
“…Stress was also measured in the clinical subjects using Heart Rate Variability (HRV), which has been reported by several clinical studies to be a strong marker of stress [87][88][89][90]. HRV as a measure of stress was significantly reduced 24.8% (p = 0.017, Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Stress is a highly complex process (e.g., chronic versus temporary stress) and not captured easily (e.g., McEwen et al, 2015). While previous research has focused on the impact of self-reported stress levels (Singh and Duque, 2012), neurophysiological tools (e.g., galvanic skin response, cardiovascular measures) and biochemical tools (e.g., measure cortisol levels) are well suited to measure different aspects of stress objectively (Föhr et al, 2015;Goyal et al, 2016;Seemann et al, 2016).…”
Section: Future Research Opportunities Related To Internal Cuesmentioning
confidence: 99%